2008
DOI: 10.1080/03079450802356938
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of a QX strain of infectious bronchitis virus in specific pathogen free and commercial broiler chickens, and evaluation of protection induced by a vaccination programme based on the Ma5 and 4/91 serotypes

Abstract: The aims of this study were firstly to evaluate the pathogenicity of an Italian isolate of the QX strain of infectious bronchitis (IB) virus using 1-day-old female specific pathogen free chicks (layer type) and 1-dayold female commercial broiler type chickens, and secondly to assess the level of protection induced in these birds by a vaccination programme including the IB Massachusetts and 4/91 serotype live attenuated vaccines. Unvaccinated birds showed clinical signs of varying severity, predominantly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
137
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 17 publications
15
137
3
1
Order By: Relevance
“…type of IBV were found (reviewed by Fabricant, 1998). The majority of the previously unknown serotypes or variants, identified in the past two decades around the world, have either disappeared or become endemic in certain geographical areas (Bochkov et al, 2006), while some of them have become widespread and predominant in the majority of the countries with a significant poultry industry over a period of time (Terregino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…type of IBV were found (reviewed by Fabricant, 1998). The majority of the previously unknown serotypes or variants, identified in the past two decades around the world, have either disappeared or become endemic in certain geographical areas (Bochkov et al, 2006), while some of them have become widespread and predominant in the majority of the countries with a significant poultry industry over a period of time (Terregino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that a vaccination schedule using a live attenuated Massachusetts (Mass) vaccine at 1 day old, followed by a heterologous live attenuated IBV vaccine at 14 days, is able to induce considerable cross-protection against challenge with a QX field strain in young specific pathogen free (SPF) birds at 35 days of age Terregino et al, 2008). However, to prevent the induction of false layers, a high level of protection is needed at a very young age.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve broad protection against damage caused by challenge with IBV variants at several weeks post vaccination, the use of different combinations of live IBV vaccines has been shown to be able to induce a high level of protection against challenges with several heterologous strains (Cook et al, 1999;Gelb Jr et al, 2005;Terregino et al, 2008), although the same combinations can be unsuccessful in inducing a satisfactory level of protection against other heterologous strains (Cook et al, 1999;Ladman et al, 2002). Several groups have shown that a vaccination schedule using a live attenuated Massachusetts (Mass) vaccine at 1 day old, followed by a heterologous live attenuated IBV vaccine at 14 days, is able to induce considerable cross-protection against challenge with a QX field strain in young specific pathogen free (SPF) birds at 35 days of age Terregino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Może to wynikać z faktu, iż pojedyncze mutacje nukleotydów w analizowanym genie S1 nie muszą wpływać na zmianę przynależności antygenowej IBV, a dodatkowo analiza przynależności genotypowej odbywa się jedynie poprzez analizę fragmentu genomu wirusa, nie uwzględniając przy tym udziału innych struktur immunogennych zaangażowanych w rozwój protekcji. Zjawiska te wykorzystywane są w terenowych strategiach uodporniania ptaków przed negatywnymi następstwami zakażenia IBV, w myśl definicji odporności protektotypowej, która zakłada, iż równoczesne wykorzystanie dwóch filogenetycznie niespokrewnionych szczepionkowych szczepów IBV skutkuje rozwojem protekcji krzyżowej w stosunku do szerokiej gamy geno-i serotypów wirusów IB (9,30,36). Immunologicznych podstaw skuteczności tej strategii uodporniania można dopatrywać się między innymi w fakcie, iż skutkuje ona silniejszą infiltracją komórek T CD8 + oraz produkcją wyższego poziomu IgA w GDO w porównaniu ze szczepionką monowalentną (6).…”
Section: Zakażenie a Szczepienieunclassified